Improving the efficiency of material flows in an Independent Timber & Builders’ Merchants Business via the implementation of a new dedicated Goods Inward/Outward facility featuring Cross-Dock methodology - Hale, Jacob (2012)
This study looks at the physical logistics challenges facing the Independent Builders’ Merchants sector within the Construction Industry Supply Chain. Against a backdrop of economic uncertainty, industry commentators have recently observed that the sector has previously accepted mediocrity in logistics because it has not understood how it can add value. The facet of on-site material flows at an exemplar Independent Builders Merchant is therefore taken as the research question to investigate whether current generic logistics techniques can be used to improve efficiency in this field.